2014
DOI: 10.1007/s11120-014-0054-0
|View full text |Cite
|
Sign up to set email alerts
|

Brassica napus responses to short-term excessive copper treatment with decrease of photosynthetic pigments, differential expression of heavy metal homeostasis genes including activation of gene NRAMP4 involved in photosystem II stabilization

Abstract: In the present study, the influence of 50 and 100 µM CuSO4 was investigated starting from 3 h till 72 h treatment of 4-weeks Brassica napus plants. High CuSO4 concentrations in nutrient medium resulted in the rapid copper accumulation in plants, especially in roots, much slower and to lower degree in leaves. Copper excess induced early decrease in the leaf water content and temporary leaf wilting. The decrease in content of photosynthetic pigments became significant to 24 h of excessive copper treatments and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…In durum wheat cultivars, chlorophyll contents decrease about 35 % in Adamello and 55 % in Ofanto cultivar over control at 20 μM Cu in the culture medium (Ciscato et al 1997). In the rapeseed of mustard plants, reduction in content of photosynthetic pigments was 35 % with excessive Cu (100 μM) treatment to 72 h (Zlobin et al 2014).…”
Section: Effect On Photosynthetic Apparatus and Pigmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In durum wheat cultivars, chlorophyll contents decrease about 35 % in Adamello and 55 % in Ofanto cultivar over control at 20 μM Cu in the culture medium (Ciscato et al 1997). In the rapeseed of mustard plants, reduction in content of photosynthetic pigments was 35 % with excessive Cu (100 μM) treatment to 72 h (Zlobin et al 2014).…”
Section: Effect On Photosynthetic Apparatus and Pigmentsmentioning
confidence: 99%
“…More recently, Zlobin et al (2014) studied the expression of four metallochaperone genes, ATX1, CCS, HIPP05 and HIPP06, involved in metal homeostasis and Cu detoxification in rapeseed. Authors observed that Cu stress activated the expression of the CCS gene in both leaves and roots, while the expression of the HIPP06 and ZIP5 genes was activated only in the roots (Wu et al 2009).…”
Section: Genotoxic Effects Of Coppermentioning
confidence: 99%
“…Hence, photosynthetic capacity of plants is compromised under Cr stress due to interaction with biosynthesis of chlorophyll molecules by inhibiting vital enzymes contributing in photosynthesis. Excessive Cr affects photosynthetic system by targeting the Calvin cycle enzymes, photosynthetic electron transport and thylakoid membrane [89]. Therefore, gradual decrease in the net photosynthetic rate can be observed in the plants treated with higher concentration of Cr [90].…”
Section: Effect Of Cr On Chlorophyll Molecules and Photosynthetic Permentioning
confidence: 99%
“…Previous studies showed that a high content of Cu in the soil causes a decrease in photosynthetic pigments [16,48]. Although Cu phytotoxicity affects both photosystems in plants, PS II is more sensitive than PS I to Cu stress [7,24,49].…”
Section: Effect Of Cu Chlorophyll Content and Gaseous Exchangementioning
confidence: 99%
“…ROS, which are toxic and remove by the activities of antioxidant compounds [18][19][20][21][22][23]. Previously, in many different crops, activities of high antioxidants were found such as in Boehmeria nivea [15], Phyllostachys pubescens [13] and Brassica napus [24] under Cu stress.…”
Section: Introductionmentioning
confidence: 99%